Morphological and molecular evolution and their consequences for conservation and taxonomy in the Le Conte's thrasher Toxostoma lecontei. (28th April 2017) - Vázquez‐Miranda, Hernán; Griffin, Josie A.; Sheppard, Jay M.; Herman, Jordan M.; Rojas‐Soto, Octavio; Zink, Robert M.
Abstract : We evaluated geographic variation and subspecific taxonomy in the Le Conte's thrasher Toxostoma lecontei by analyzing DNA sequences from 16 nuclear loci, one mitochondrial DNA locus, and four study skin characters, and compared these data sets with previously published data on plumage coloration and different mtDNA genes. Morphological support for the southernmost taxon, T. l. arenicola, is relatively weak: multivariate analyses of morphometrics or back coloration do not provide diagnostic support, although one color character differs statistically. However, combined DNA analyses indicate that T. l. arenicola is diagnosable and reciprocally monophyletic, diverging from T. l. lecontei at least 140 000 yr ago. Little to no past introgression across a very short geographic distance despite the long period of isolation is strong evidence of independently evolving taxa. We suggest that the lack of morphological divergence in traits related to niche use has prevented the two taxa from invading each other's range. Despite relatively weak morphological differences we suggest that these two deeply divergent lineages merit species status, and we suggest Vizcaíno thrasher for the common name corresponding to T. l. arenicola . The population size of T. l. arenicola is small and the taxon is in need of preservation attention.